Chronic Kidney Disease: Homeopathy Can Provide Solace (Homoeopathy for All, 2023)
Chronic Kidney Disease (CKD)  is a progressive and potentially  debilitating condition that affects  millions of people worldwide. It  is characterized by the gradual  loss of kidney function over an  extended period, leading to the  glomerular filtration rate (eGFR)  and the presence of kidney damage.  The eGFR measures how well the  kidneys filter waste from the blood  and is expressed in milliliters per  minute per 1.73 square meters (m²)  of body surface area. The stages are  defined as follows:
Keywords: Disease; body; milliliters